Clinical Implications of 18F-FDG PET/CT in Malignant Glomus Tumors of the Esophagus. (June 2020) - Seban, Romain-David; Bozec, Laurence; Champion, Laurence
Abstract : Abstract: The majority of glomus tumors are localized to cutaneous sites and are benign. However, extracutaneous malignant glomus tumors have been reported and are aggressive. Here, we report a case of a 45-year-old man who presented severe dysphagia, diagnosed with malignant glomus tumor of the esophagus. 18 F-FDG PET/CT played a decisive role in several phases of the patient management offering previously unknown accuracy. It was first performed in the initial staging of local tumor extent before surgery. A year and a half after, 18 F-FDG PET/CT helped to detect recurrence and, finally, was performed for response evaluation of several systemic therapies.